McGraw Hill's National Electrical Safety Code (NESC) 2023 Handbook - Marne, David J.; Palmer, John A. (New York McGraw-Hill, 2023)
Up-to-date, rule-by-rule clarification of every requirement in the 2023 NESCThis one-stop resource thoroughly explains how to apply and meet the NESC rules for electrical supply stations and equipment, as well as overhead and underground electric supply and communications lines. The book offers concise summaries of complicated, confusing, and sometimes controversial issues. Hundreds of diagrams, photos, and practical examples are contained in this comprehensive guide.Designed to be used as a companion to the code itself, McGraw Hill's National Electrical Safety Code (NESC) 2023 Handbook has been fully updated to reflect the changes in the 2023 NESC. You will gain access to straightforward, ready-to-apply code clarification, enabling you to work safely and efficiently and achieve full compliance.Offers a comprehensive rule-by-rule overview of the 2023 NESCIncludes examples of code application, including examples new to this editionWritten by experienced electrical engineers and NESC experts.
Electronic reproduction
Keywords: Computer Science; Computers; Electronic books